(untitled) (Scientific journal of the Fergana State University, 2023)
The article discusses biological processes, including the law of bacterial reproduction, the law of cell growth in time, the law of cell destruction in a sound field, the speed of muscle contraction using ordinary differential equations. When studying this problem, the importance of differential equations in the construction of mathematical models of various biological processes is emphasized.